Effect of camu camu flour on acetaminophen-induced liver damage in mice - Santa Cruz-Vega, Katia (2021)
Objectives. To evaluate the effect of Myrciaria dubia (camu camu) flour on liver tissue induced to acetaminophen toxicity in mice. Methods. Experimental design. A suspension of camu camu flour (HCC) with 1.6% starch was prepared. 40 male mice of the BALB/c strain were used, with an average weight of 30.8 g and two months of age, which were divided into five groups, receiving the following treatment, orogastric route, for a period of 10 days, groups I and II: 1.6% starch 10 mL / kg; group III: HCC 200 mg / kg, group IV: HCC 500 mg / kg and group V: HCC 800 mg / kg. On the 6th day of treatment, acetaminophen (300 mg / kg) was administered to groups II-V until the 10th day. After the intervention, the animals were fasted for 12 hours, to then be sacrificed after anesthesia with sodium pentobarbital. The liver was removed, the greater lobe was identified and sectioned for biochemical and histological study. Results. The camu camu flour reduced the levels of the hepatic index, and presented a better profile of the glutathione system, compared to group II; however, the lipoperoxidation figures did not show a significant difference. At the histological level, in the groups that received HCC, binucleated hepatocytes were observed, as well as a greater maintenance of polarity; however, some samples showed microvacuoles and slight chromatin fragmentation. Conclusion: Camu camu flour showed a hepatoprotective effect against acetaminophen toxicity in mice.